Reflection of Social Care Worker ’ s Image in the Press - Vītoliņa, Kristīne; Erkena, Dace; Gulbe, Dagnija; Rozentāle, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Quality of life is one of indicators describing the development of society and it is influenced by several factors. One of these factors is job. For the major part of society it is important to work in the profession possessing positive character and promoting increase of persons’ self-assessment. Perception of the character in society is particularly important in branches and for specialists whose professional activities are connected with the provision of services for different groups of population. In order to evaluate the character of social care was carried out a study. Aim of the study was to analyze common and different characteristic peculiarities of the character of social care in publications available in the press. Obtained results were analyzed and conclusions possible to utilize in order to improve the character of social care and encourage self-assessment of specialists working in this sector were performed.